2022
DOI: 10.3390/ijms23031331
|View full text |Cite
|
Sign up to set email alerts
|

Chronoradiobiology of Breast Cancer: The Time Is Now to Link Circadian Rhythm and Radiation Biology

Abstract: Circadian disruption has been linked to cancer development, progression, and radiation response. Clinical evidence to date shows that circadian genetic variation and time of treatment affect radiation response and toxicity for women with breast cancer. At the molecular level, there is interplay between circadian clock regulators such as PER1, which mediates ATM and p53-mediated cell cycle gating and apoptosis. These molecular alterations may govern aggressive cancer phenotypes, outcomes, and radiation response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 161 publications
(244 reference statements)
0
7
0
1
Order By: Relevance
“…As a result, during the dark phase melatonin triggers cellular and molecular mechanisms that are expressed only after cessation of the melatonin signal during the following day. Recent studies have reported that biorhythm disorders are closely associated with BC incidence and progression [ 69 ]. For example, the circadian gene TIMELESS was found to be highly expressed in BC conditions, predicting a poor prognosis (e.g., tumor growth) after positive regulation of sphingolipid metabolism [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, during the dark phase melatonin triggers cellular and molecular mechanisms that are expressed only after cessation of the melatonin signal during the following day. Recent studies have reported that biorhythm disorders are closely associated with BC incidence and progression [ 69 ]. For example, the circadian gene TIMELESS was found to be highly expressed in BC conditions, predicting a poor prognosis (e.g., tumor growth) after positive regulation of sphingolipid metabolism [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…To determine the best cutoff value for DPT based on LC, we used the Youden method. Means between the 2 groups thus defined were compared with a Student t test and proportions with a χ 2 test. To normalize their distribution, some variables were log-transformed.…”
Section: Methodsmentioning
confidence: 99%
“…Time plays a crucial role in radiation oncology (RO), sometimes in unexpected ways (FLASH–radiation therapy [RT], 1 chrono-RT 2 ). In the treatment of cancer, by definition a progressive disease, avoidance of delays is essential.…”
Section: Introductionmentioning
confidence: 99%
“…The cell cycle, proliferation, and cell death are closely intertwined with the circadian rhythm. Several recent studies have provided compelling evidence on the association between the circadian cycle and cancer; similar to healthy cells, tumor cells are rhythmic ( 9 , 10 ), and their growth depends on circadian rhythms ( 11 ). It has been reported that each phase of the cell cycle corresponds to a different degree of radiosensitivity ( 12 ).…”
Section: Introductionmentioning
confidence: 99%